2014
DOI: 10.1177/016264341402900102
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Text-to-Speech on Expository Reading for Adolescents with LD

Abstract: Text-to-speech (TTS) technology holds promise as a compensatory tool for adolescents with learning disabilities in accessing grade-level expository text. A multiple-baseline-across-participants design examined the effectiveness of TTS on oral reading fluency, comprehension, and task completion time for two males and one female with reading disabilities in a Midwest junior high school. TTS did not affect students' fluency, comprehension, or task completion time, although social validity interviews revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…The authors concluded that a multifunctional app might be beneficial for decoding ability as well as motivation for future studies. Other recent studies have also emphasized the benefit of using TTS for struggling readers, especially from a student perspective, for example, accessability to text and confidience in the classroom setting [21][22][23][24][25]. In a pilot study [12], 35 students aged 10-12 years with documented reading and writing difficulties (of which 30% diagnosed were with dyslexia) participated.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that a multifunctional app might be beneficial for decoding ability as well as motivation for future studies. Other recent studies have also emphasized the benefit of using TTS for struggling readers, especially from a student perspective, for example, accessability to text and confidience in the classroom setting [21][22][23][24][25]. In a pilot study [12], 35 students aged 10-12 years with documented reading and writing difficulties (of which 30% diagnosed were with dyslexia) participated.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary practitioners should include technology that uses bimodal support (i.e., auditory and visual) when delivering curriculum to struggling readers to see the effects on student engagement. My study is similar to previous research which revealed that participants felt TTS helped them read longer and be more engaged (Meyer & Bouck, 2014). As shown with Dianna and Jack, if students use TTS to increase reading comprehension, they may learn better and more efficiently.…”
Section: Maintaining Reading Comprehension Performancesupporting
confidence: 87%
“…In comprehension quizzes after reading assignments associated with the intervention, no improvement was seen over the six weeks of intervention for the six students in the middle grades. In another study with a text-to-speech tool [13], three students with reading disabilities at the high school level used the tool while reading in seven to eleven sessions in a multiple baseline design. Though no improvement was seen in comprehension or reading fluency, students reported that the tool helped them and improved their completion time for the comprehension quizzes.…”
Section: Read Aloud Toolsmentioning
confidence: 99%